Effect of destination management on tourism destination competitiveness in devolved governance after COVID-19: a case of Kakamega County - Musee, S. M. (Strathmore University, 2023)
Kakamega County is one of Kenya’s devolved units. It is an emerging destination in one of the lowly ranked tourism competitive regions of the Western Tourism Circuit. Similar to other destinations, Kakamega was adversely affected by the Covid-19 pandemic. The study’s main objective was to determine the effect of destination management on the tourism destination competitiveness of Kakamega County in Kenya’s devolved governance in the aftermath of Covid-19. Specific objectives were to determine the effect of tourism policy in enhancing the tourism destination competitiveness of Kakamega County after COVID-19; establish the influence of destination marketing in promoting tourism destination competitiveness of Kakamega County after COVID-19; and, evaluate the effect of environmental sustainability management in fostering tourism destination competitiveness in Kakamega County after COVID-19. Porter’s theory of competitive advantage of nations and sequential theory of decentralisation provided a theoretical foundation for the study. On the other hand, Dwyer and Kim’s model of competitiveness enhanced the conceptualisation of the link between destination management and competitiveness. An interpretivism philosophy informed the adoption of a descriptive survey research design. Stratified purposive sampling targeted a sample size of 50 tourism and hospitality practitioners in the public and private sectors in Kakamega County. Data was collected using a close-ended questionnaire. Multi linear regression analysis was used to establish that the construct of destination management, that is, tourism policy, destination marketing and environmental sustainability all had a moderate and positive effect on tourism destination competitiveness. Overall, destination management had a moderate and positive effect on the competitiveness of Kakamega County as a tourism destination. The study recommends community inclusion in tourism ventures in Kakamega county; adequate resource allocation to tourism and travel sector development; regular market intelligence to understand current tourism trends in competitor destinations to integrate destination marketing in all tourism product development phases; and, entrenched sustainable tourism through better environmental management and conservation of unique natural and cultural heritage tourism attractions. The study proposed a need for further research on tourism destination competitiveness in devolved units based on other indicators and determinants like decentralised governance policy. Keywords: Tourism Destination Competitiveness; Destination Management; Devolved Governance
Full- text thesis